EXPRESSIVE SPEECH ACTS IN THE STATUSES OF THE FACEBOOK USERS - Widdya Syafitri (English Letter Department, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
This research is conducted based on two purposes; they are to identify the types of expressive speech act found in the statuses of the Facebook users, and to explain the modes of expressive utterance used in the statuses. Therefore, the data source is the social network that is Facebook and the data are the statuses of the Facebook users. The data are collected by using observational method, followed by non-participant observational technique and taking-note technique. The data analysis is based on pragmatic identity method proposed by Sudaryanto (2015) which is also supported by the theory of the types of expressive speech act by Ronan (2015), and theory about the modes of utterance from Alwi, et al (2000). The analysis result shows that there are fourteen types of expressive speech act in the statuses. They are the expression of agreement, disagreement, apology, gratitude, sorrow (sadness), exclamation (complaint), volition (hope), anger, disappointment, encouragement, satire, annoyance, pride, and congratulation. Meanwhile, the modes of expressive speech act that are used consist of declarative mode, interrogative mode, and exclamative mode. The importance of this research is to reveal or show that there is something else the Facebook users want to say behind their statuses. Sometimes, they do not really state what they mean in their statuses. They use indirect way and there lies the use of expressive speech act which can be stated in different way.